Is dispositional optimism associated with endometriomas and deep infiltrating endometriosis? - Inés Morán-Sánchez; Evdochia Adoamnei; María Luisa Sánchez-Ferrer; María Teresa Prieto-Sánchez; Julián Jesús Arense-Gonzalo; Virginia Casanova-Mompeán; Ana Carmona-Barnosi; Jaime Mendiola; Alberto Manuel Torres-Cantero (Taylor & Francis Group, 2021)
Introduction Endometriosis is a chronic painful condition characterized by high prognostic uncertainty, as well as the threat of infertility and emotional symptoms that may affect many aspects of women, including psychological characteristics like dispositional optimism. Considering the impact of endometriosis on psychological health and the paucity of papers on this topic, the aim of this study is to explore optimism and associated factors in endometriosis. Methods A case-control study was performed on a group of 95 women with endometriosis and 156 controls. All participants completed the Life Orientation Test-Revised (LOT-R), a self-administered tool for assessing dispositional optimism. Pain severity, medication, gynecological and socio-demographic information was also collected. Results Low optimism was observed for women with endometriosis compared to controls even after covariate adjustment (LOT-R global scores: 14.5 vs. 15.9 points, p = .045). Conclusions This study provides the first evidence that a personality dimension with many prognostic implications may be altered in women with endometriosis. Our findings highlight the importance of a broader understanding of this condition, treating this disorder from a biopsychosocial perspective and suggests the need for non-medical attention within a multidisciplinary team.